The Third Way : a Plea for a Balanced Cannabis Policy. - Fijnaut, Cyrille J. C. F. (Nijhoff law specials., 2015)
What is sensible when it comes to developing and implementing a policy with regard to products which in the case of regular use are harmful, but which at the same time exert a strong attraction, even so strong that people (may) become dependent on or addicted to them? This question relates to many illicit drugs, but these days it is, both nationally and internationally, mainly related to the policy regarding the production, distribution and consumption of cannabis. Generally speaking, the legalization of cannabis in Uruguay and in some states of the United States of America, in particular Colo.